The dimensions of written expression: Language group and gender differences. (February 2015) - Babayiğit, Selma
Abstract: This study compared the written expression of 159 English-speaking first (L1) and second language (L2) learners ( M age = 9; 7 years, SD = 3.63 months) in England The L1 learners outperformed their L2 peers on the four dimensions of written expression, namely holistic quality, written vocabulary, organisational quality, and compositional fluency. Girls also outperformed boys on all dimensions, except for organisation. The interaction between language group and gender was nonsignificant, but there was a trend for the language group differences to be larger for boys. Vocabulary, organisation, and compositional fluency made unique contributions to holistic quality in both language groups and the strength of these relations were relatively comparable across the L1 and L2 groups. Educational implications are discussed. Highlights: The first language ( learners outperformed the second language learners on all dimensions of written expression. Girls outperformed boys on all dimensions, except organisation. Vocabulary, organisation, and compositional fluency predicted holistic quality in both language groups. The strength of relations was invariant across the two language groups.